161k views
0 votes
Solve the equation √x+√(x+3)=3.

1 Answer

6 votes

Answer:

The solution for this question is 1.

Explanation:

Given that

√x+√(x+3)=3.

√x=3-√(x+3) (a) simplify the equation

square equation (a)

(√x)^2=(3-√(x+3))^2

we know that (a-b)^2=(a^2+b^2-2.a.b) and (√x)^2=√x*√x=x .So solve equation a

(√x)^2=(3-√(x+3))^2

x=(3)^2+(√(x+3))^2-2*√x+3*3

x=9+(x+3)-6√x+3

x=9+x+3-6√x+3 simplify equation

x-x=9+3-6√x+3

0=12-6√x+3

6√x+3=12

√x+3=12/6

√x+3=2 (b)

square equation b

(√x+3)^2=2^2

x+3=4

x=4-3

x=1

User Ilan Klinghofer
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.